SELF-ASSESSMENT SKILLS AMONG ACADEMIC LEADERS A CASE STUDY: JERASH UNIVERSITY, JORDAN - Mohammad Hasan Jaradat (European Scientific Journal, ESJ, 2012)
The study aims at identifying the level of self-assessment skills among the academic leaders at Jerash University – Jordan. In order to achieve the objective of the study, a questionnaire was handed out to 30 respondents (deans and departments heads) at Jerash University. Following the data collection and processing, findings revealed that the level of self-assessment skills among the sample population was intermediate in general while planning, implementation and evaluation skills ranked at a higher level. The study makes numerous recommendations, including running training workshops on the procedures of self-assessment studies.